ETHICAL IMPLICATIONS OF THE ADVOCATE PROFESSION IN LAW ENFORCEMENT IN INDONESIA - Rolando Marpaung; Micael Jeriko Damanik; Dikki Saputra Saragih; Sherhan; Desniar Dachi (Journal of International Islamic Law, Human Right and Public Policy, 2024)
A code of ethics is the implementation of guidelines or guidelines for behavior that have been outlined by a professional code of ethics. The purpose of this research is to find out the role of legal professional ethics in law enforcement efforts in Indonesia. To find out what the function of the Indonesian Advocate Code of Ethics is for advocates in carrying out their profession. This type of research is normative juridical legal research. Normative juridical legal research is research that conceptualizes law as what is written in statutory regulations or laws as rules or norms which are benchmarks for human behavior that is considered appropriate. Conclusion The code of ethics for the legal profession plays a very important role for Advocates in law enforcement. Ethics is essentially a view of life and guidelines on how people should behave.